The Drosophila mushroom body is a quadruple structure of clonal units each of which contains a virtually identical set of neurones and glial cells. - Ito, K.; Awano, W.; Suzuki, K.; Hiromi, Y.; Yamamoto, D. (Development, 1997)
The mushroom body (MB) is an important centre for higher order sensory integration and learning in insects. To analyse the development and organisation of the MB neuropile in Drosophila, we performed cell lineage analysis in the adult brain with a new technique that combines the Flippase (flp)/FRT system and the GAL4/UAS system. We showed that the four mushroom body neuroblasts (MBNbs) give birth exclusively to the neurones and glial cells of the MB, and that each of the four MBNb clones contributes to the entire MB structure. The expression patterns of 19 GAL4 enhancer-trap strains that mark various subsets of MB cells revealed overlapping cell types in all four of the MBNb lineages. Partial ablation of MBNbs using hydroxyurea showed that each of the four neuroblasts autonomously generates the entire repertoire of the known MB substructures.